2017
DOI: 10.1049/iet-nbt.2016.0107
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structural characterisation and release study of novel hybrid microspheres entrapping nanoselenium, produced by green synthesis

Abstract: The main goal of this study was to synthesise and characterise different formulations based on alginate and alginate/chitosan microspheres containing nanoselenium (nano-Se) for controlled delivery applications. Nanosize elemental selenium was produced by using probiotic yogurt bacteria () in a fermentation procedure. The structural and morphological characterisation of the microspheres was performed by Fourier transform infrared (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…5b) which suggests that the nanoparticles are not crystalline. Some previous studies related to crystalline phase investigation of selenium nanoparticles suggested that stable amorphous forms (or even low crystallinity) are advantageous for biological applications, as they exhibit better solubility and [32,33].We consider that this method is suitable for different biological applications such drug release, functional food or nutritional supplements, being not only facile and rapid, but also very safe for the environment and low cost.…”
Section: Morphological and Structural Characterization Of Selenium Namentioning
confidence: 99%
“…5b) which suggests that the nanoparticles are not crystalline. Some previous studies related to crystalline phase investigation of selenium nanoparticles suggested that stable amorphous forms (or even low crystallinity) are advantageous for biological applications, as they exhibit better solubility and [32,33].We consider that this method is suitable for different biological applications such drug release, functional food or nutritional supplements, being not only facile and rapid, but also very safe for the environment and low cost.…”
Section: Morphological and Structural Characterization Of Selenium Namentioning
confidence: 99%
“…Several types of bacteria and cyanobacteria cultivated in submerged cultures have already been used for the biosynthesis of SeNPs, and these include Escherichia coli [366], Enterobacter cloacae [367], Pseudomonas aeruginosa [368], Klebsiella pneumoniae [369], Zooglea ramigera [370], Lactobacillus casei [371], Streptomyces sp. [372], Arthrospira [Spirulina] platensis [373], and many others.…”
Section: Encapsulation Of Nanoselenium Particles Into Polysaccharidesmentioning
confidence: 99%
“…Selenium is an essential trace mineral in humans that is involved in the maintenance of health and growth (Cavalu et al ., 2017; Qiu et al ., 2018; Nastulyavichus et al ., 2019). It has various physiological roles in humans such as acting as antioxidant, preventing the formation of tumours and immune regulation (Yan et al ., 2018; Tang et al ., 2019).…”
Section: Selenium Nanoparticlesmentioning
confidence: 99%